Možnosti prihodnjega razvoja normativnih podatkov v sistemu COBISS / Perspectives for the future development of authority data in the COBISS system - Andreja Krajnc Vobovnik (Organizacija Znanja, 2023)
By introducing the IFLA Library Reference Model, the significance of authority control is constantly increasing as authority data will play a key role in the linked data network. Consequently, the preparation of authority data will help when implementing IFLA LRM and will prove useful during the transition to RDA (Resource Description and Access). The overview of authority data situation in the COBISS.net system with the focus on the Slovenian COBISS.SI system is presented. In addition to this, the options of further development of authority records are indicated. The situation in CONOR.SI and SGC authority databases as well as the enrichment of authority records for personal names and for corporate body names with identifiers are described. Additionally, plans for the transition to a new catalogue based on the IFLA LRM conceptual model are indicated.